2022
DOI: 10.1039/d2ra00386d
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly resolved, label-free nucleic acid sensing at solid–liquid interface using non-ionic DNA analogues

Abstract: Improved nucleic acid sensing in terms of single nucleobase mismatch discrimination, as achieved by the surface-confined non-ionic PNA and MO capture probes, is exemplified by single molecule force spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…10,11 PMOs are not limited to work only as antisense agents, their applications in nanotechnology and surface hybridization are growing. 12–17 Due to the presence of a neutral backbone and a cyclic six-membered morpholino ring, we have observed that a PMO enhances the binding affinity toward the complementary strand of DNA. 17,18 Further improvement of the hybridization of a PMO could be achieved by the incorporation of nucleobase functionalized morpholino nucleotides into the PMO, as observed in the case of DNA/RNA where the thermal stability was increased by an enhanced П-stacking interaction with the target RNA, 19–28 and the gene silencing effect was also improved.…”
Section: Introductionmentioning
confidence: 96%
“…10,11 PMOs are not limited to work only as antisense agents, their applications in nanotechnology and surface hybridization are growing. 12–17 Due to the presence of a neutral backbone and a cyclic six-membered morpholino ring, we have observed that a PMO enhances the binding affinity toward the complementary strand of DNA. 17,18 Further improvement of the hybridization of a PMO could be achieved by the incorporation of nucleobase functionalized morpholino nucleotides into the PMO, as observed in the case of DNA/RNA where the thermal stability was increased by an enhanced П-stacking interaction with the target RNA, 19–28 and the gene silencing effect was also improved.…”
Section: Introductionmentioning
confidence: 96%
“…Consequently, applications of the XNAs as nucleic acid hybridization probes have been realized in a number of applications (see Table ). ,,, Because LNA, PNA and MO are the most popularly used XNAs with modified backbones, their applications as hybridization probes in the construction of advanced NABs will be presented here.…”
Section: The Xnas As Troubleshootermentioning
confidence: 99%
“…Important developments in the field of novel nucleic acid‐like polymers have already been in research pipelines for years under different names and are collectively known as xenonucleic acids (XNA) of various kinds (see Chaput & Herdewijn, 2019; Alenaizan et al, 2021; Chaput, 2021; Mana, Kundu, et al, 2022, for recent explorations). While this work is currently developing in many interesting avenues, we can be sure that completely different chassis will be used before long.…”
Section: From the Proof Of Concept To The Construction Of Living Cellsmentioning
confidence: 99%